Human capital, structural capital, and relational capital: effects on firm performance in indonesian manufacturing companies (2023–2024) - Marshanda Sisilia Tangka; Priscillia Weku (Riset Akuntansi dan Manajemen Pragmatis, 2026)
This study examines the effect of human capital, structural capital, and relational capital on firm performance in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2023–2024 period. A quantitative approach was applied using multiple linear regression analysis. Using purposive sampling, 70 companies were selected, yielding 140 firm-year observations. The independent variables, human capital, structural capital, and relational capital, were measured using the Modified Value Added Intellectual Coefficient (M-VAIC) approach, while the dependent variable, firm performance, was proxied by Return on Assets (ROA). The results show that human capital has no significant effect on firm performance (t = 0.551, p = 0.583), whereas structural capital (t = 2.337, p = 0.021) and relational capital (t = 2.675, p = 0.008) have a positive and significant effect. The three variables jointly explain 9.5% of the variation in ROA (Adjusted R² = 0.076; F = 4.786, p = 0.003). The findings support Resource-Based Theory by showing that internally developed systems and externally oriented stakeholder relationships are, in this sample and period, more consistently associated with financial performance than human capital alone. Companies are advised to strengthen structural and relational capital as strategic resources while continuing to invest in human capital development to support long-term, sustainable performance.